Maternal pre-pregnancy body mass index and circulating microRNAs in pregnancy. Issue 4 (July 2017) - Enquobahrie, Daniel A.; Wander, Pandora L.; Tadesse, Mahlet G.; Qiu, Chunfang; Holzman, Claudia; Williams, Michelle A.
Summary: Background: Maternal pre-pregnancy overweight and obese status has been associated with a number of pregnancy complications and adverse offspring outcomes. Mechanisms for observed associations, however, are largely unknown. We investigated associations of pre-pregnancy body mass index with early-mid pregnancy epigenetic biomarkers, circulating microRNAs. Methods: Peripheral blood was collected from participants (16–27 weeks gestation) of two multi-racial pregnancy cohorts, the Omega Study and the Pregnancy Outcomes and Community Health Study. Plasma miRNA expression was characterised using epigenome-wide (319 miRNAs) profiling among 20 pregnant women in each cohort. Cohort-specific linear regression models that included the predictor (pre-pregnancy body mass index), the outcome (microRNA expression), and adjustment factors (maternal age, gestational age at blood collection, and race) were fit. Results: Expression of 27 miRNAs was positively associated with pre-pregnancy body mass index in both cohorts (p-values <0.05). A number of these differentially expressed miRNAs have previously been associated with adipogenesis (e.g. let-7d*, miR-103-2*, -130b, -146b-5-p, -29c, and -26b). Identified miRNAs as well as their experimentally validated targets participate in pathways that involve organismal injury, reproductive system disease, connective tissue disorders, cancer, cellular development, growth and proliferation. Conclusion: Pre-pregnancy body mass index is associated with circulating miRNAs in early-mid pregnancy.